PENGARUH MOTIVASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA BUSINESS CENTER BINA NUSANTARA DI JAKARTA BARAT - Emil; Supardi, Yusuf (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of motivation and work stress on employee performance at the Bina Nusantara Business Center in West Jakarta. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 54 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are motivation has a significant effect on employee performance with a determination coefficient value of 46,9% and hypothesis testing obtained t count > t table or (6.779 > 2.009) and a significance of 0.000 <0.05. Work stress has a significant negative effect on employee performance with a coefficient of determination of 45,6% and hypothesis testing obtained t count > t table or (-3.693 > -2.009) and a significance of 0.001 <0.05. Motivation and work stress simultaneously have a significant effect on employee performance with the regression equation Y = 26.023 + 0.485X1 - 0.150X2. The coefficient of determination is 20,8% while the remaining 40.5% is influenced by other faktors. Hypothesis testing obtained F count > F table or (37.391 > 2.790) and a significance of 0.000 <0.05.